Temperature effects on seed germination and seedling biochemical profile of cannabis landraces - Langa, Sabeliwe; Magwaza, Lembe Samukelo; Mditshwa, Asanda; Tesfay, Samson Zeray (MDPI, 2024)
This study investigated the effect of temperature on the germination and seedling biochemical profiles of eight cannabis landraces, namely Ladysmith Ugwayi wesiZulu (L1) and Iswazi (L2), Durban Poison (H1), Bergville Ugwayi wesiZulu (B1), Natal (B2), and Iswazi (B3), and Msinga Ugwayi wesiZulu (M1) and Iswazi (M2). Seed viability, germination rate, and germination percentage were evaluated along with seedling amino acids, carbohydrates, and fatty acids methyl esters (FAMEs) under day/night temperature regimes of 20/15 °C, 30/25 °C, and 40/35 °C. Results showed a significant effect (p < 0.001) of temperature on germination percentage, rate, and biochemical profiles of cannabis landraces. Landraces L1, B1, H1, B2, and M1 had higher germination at 20/15 °C, while B3, M2, and L2 performed better at 30/25 °C. Biochemical profiles varied with temperature and landraces. Amino acid content increased with temperature but did not correlate with germination indexes. Carbohydrates and FAMEs decreased with rising temperature, peaking at 30/25 °C. FAMEs strongly correlated with germination indexes, linking lipid composition to seed performance. Sorbitol positively correlated with germination, while glucose and fructose showed indirect correlations. This study underscores the impact of temperature on germination and the biochemical profiles of cannabis landraces, highlighting the importance of considering genotype-specific responses in varietal selection.
Keywords: 3108 Plant Biology; 31 Biological Sciences; physiology; seed germination index; amino acids; membrane fluidity; fatty acids; carbohydrates